PENERAPAN COMPUTER BASED CUSTOMER RELATIONSHIP MANAGEMENT PADA PT. XYZ - Budi Wasito, Humdiana (Institut Bisnis dan Informatika Kwik Kian Gie, 2017)
The development of information system has made people easier for getting information also share the information, especially since internet was made, getting any the information is easier and faster. Customer information system design using some theoretical support for the system run in accordance with the topic of writing that created that is a customer information system design.Stage method of data collection using questionnaires, interviews and observation at PT. XYZ. Interviews were conducted by asking question directly. The result of this research will be developed into a new system that will generate an information about Customer Relationship Management PT. XYZ Indonesia using the system development life cycle, DFD context, DFD 0, DFD Detailed, and Entity Relationship Diagram. The conclusion of this study is a Customer Relationship Management application which can help PT. XYZ in getting accurate reports as well as information and can live a good relationship with customers, increase customer loyalty and relationships with business partners.Â Keywords : Customer Relationship Management, System Development Life Cycle